Simulation of coupled impact-management response scenarios for distributed wastewater environmental discharges at basin scale through urban environmental risk network transmission mechanism. - Liu, Gengyuan; Casazza, Marco; Lega, Massimiliano (Journal of Environmental Management, 2019)
Abstract A multi-agent modeling method is applied here to model the coupled environmental impact and management response scenarios in relation to the impact of multiple wastewater discharges at river basin scale. Based on the Netlogo modeling platform, the cumulative impact of water pollution, which was represented here by COD values, is esteemed using Huaihe River Basin (China) as a case study. As a novel factor, different management responses to the adverse effects of cumulative pollution level increases along the river are also considered in the simulation processes. Based on 45 alternative scenarios, the model displayed its ability to represent the coupled dynamics along time between pollution propagation and management actions (described according to their occurrence, responsiveness and characteristics). Besides the most trivial results, which demonstrate the efficacy of the model in representing the simulated reality, an interesting result is that, the management responses to pollution propagation are more effective when the river basin authorities do not take any coercive policies. This might depend on the fact that excessive restraints have a dependence on their underlying mechanism, thus limiting a spontaneous reaction to pollution episodes. It is important, however, to stress the role of ecological education, in parallel to management, to limit the necessity of top-down approaches in the river system management measures. Highlights • Multi-agent model is applied to test coupled environmental impact and management responses. • Effects of different management responses to cumulative pollution along a river are tested. • Management responses are more effective when coercive policies are avoided.